Kualitas produk dan persepsi harga terhadap keputusan pembelian melalui minat beli sebagai variabel intervening - Yudha Pratama Putra; Hari Purwanto; Liliek Nur Sulistiyowati (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
The research is to examine and determine the effect of product quality and price perception on purchasing decisions, as well as to examine the role of buying interest as a mediation. This type of research is quantitative research, the number of samples used is 100 customers of UMKM Roti Bolu Dinawa Magetan, which is taken by purposive sampling method. Collecting data using a questionnaire with direct distribution to respondents. The questionnaire was prepared using a 5-point Likert Scale, and data analysis using Path Analysis. The results of the study reveal that product quality has no effect on purchasing decisions through buying interest. If product quality increases, buying interest and purchasing decisions for Roti Bolu Dinawa will also increase.